PENGELOLAAN KELAS YANG RAMAH ANAK PADA MASA PANDEMI COVID19 - Sholeh, Muhammad (UIN Sumatera Utara, 2021)
Classroom management towards being child-friendly is an important thing that teachers do especially during these Covid19 pandemic, where the possibility of ignoring children's rights in the learning process is very open to occur. This study aims to describe the role of teachers in classroom management during the Covid19 pandemic at MI Miftahul Huda Banyumas. This is descriptive qualitative research and using observation, interviews and documentation. The results showed: first, the lesson plan was prepared by paying attention to the differences in the potential of students and the use of certain media in the learning process. Second, in learning process the teacher pays attention using polite words or sentences to students, using proactive learning strategies, and the handling of disciplinary behavior in students without discrimination and violence. Third, when reflecting on learning, especially related to limitations in learning and the level of enthusiasm of students. The effects are the students become more focused on listening to the teacher's explanation, doing the assignments given by the teacher, doing practice according to the teacher's directions and following the ice breaking activities carried out by the teacher, and it doesn't seem that the students are afraid and threatened to take part in learning.